Cultural heritage management, the Polish experience - Arpentii, Irina (Plural: History, Culture, Society, 2017)
This article aims to understand the concept of cultural heritage and to analyze its appropriation by contemporary society through an efficient management, based on the Polish experience. This article presents the definition of cultural heritage. It also discusses the laws, concerning heritage and the cultural heritage management system in Poland. This is a contribution to the general aspect of cultural heritage management. I have highlighted the role of documentation for the identification, protection, interpretation, and preservation of cultural heritage. Referring to digitalization, the information about digitization projects is also examined, such as Kultura+ Program and Arches. To better assess and evaluate the cultural heritage management in Poland, I have presented some of the best practices, such as the Wieliczka protection, Wawel conservation and Warsaw’s Historic Centre reconstruction and demonstrated the role of cultural institutions and organizations for the protection and promotion of cultural heritage.